Prognostic Value and Clinical Impact of Pretreatment FDG PET in Pulmonary Lymphoepithelioma-Like Carcinoma. (February 2019) - Su, Tzu-Pei; Ho, Kung-Chu; Wang, Chih-Wei; Lin, Chun-Yu; Liu, Chien-Ying; Yang, Cheng-Ta; Yen, Tzu-Chen
Abstract : Purpose: Compared with other forms of non–small cell lung cancer, pulmonary lymphoepithelioma-like carcinoma (LELC) is rarer and portends better outcomes. We sought to investigate the prognostic role and clinical impact of pretreatment 18 F-FDG PET in pulmonary LELC. Methods: A total of 71 patients with pulmonary LELC were identified through a retrospective review of clinical records. Of them, 41 underwent 18 F-FDG PET for primary staging. Outcomes were assessed using the Kaplan-Meier method and Cox regression models with a forward stepwise selection procedure. Staging changes served as the main outcome measure for assessing the impact of 18 F-FDG PET. For the purpose of analyses, all patients were restaged according the American Joint Committee on Cancer Staging Manual eighth edition. Results: Stage and pretreatment 18 F-FDG PET were significantly independent predictors of overall survival (OS) on multivariate analysis. Five-year OS rates for patients with stages I–II, III–IVA, and IVB were 92.3%, 70.4%, and 20.0%, respectively. The use of 18 F-FDG PET for staging purposes was associated with a better OS ( P = 0.003). Specifically, the 5-year OS rates for patients who were staged with and without 18 F-FDG PET were 85.4% and 49.7%, respectively ( P = 0.012). 18 F-FDG PET resulted in a disease upstage in 28.6% of patients with CT-defined stages III–IVA; of them, 14.3% were upstaged to IVB disease. Conclusions: The American Joint Committee on Cancer eighth edition stage and pretreatment 18 F-FDG PET were independent prognostic factors for OS in patients with pulmonary LELC. 18 F-FDG PET imaging resulted in a better disease staging with a corresponding optimization of therapeutic interventions, which ultimately improved survival outcomes.